Standing on the shoulders of programmers. (December 2021) - Rao, Achintya
Abstract : Free and open-source software is growing to be a powerful tool in academic research, helping scientists to collaborate better and work smarter. Achintya Rao investigates how such software is being used in physics research, and its role in the wider open-science movement.